(untitled) (Homoeopathy for All, 2024)
Obsessive-compulsive disorder (OCD) is a chronic mental illness in which a person experiences ir rational, recurrent thoughts (obses sions), engages in irrational, re petitive activities (compulsions), or both. Homeopathy is one of the most popular supplemental medi cal practices. In homoeopathy, the principle of individualization serves as the foundation for remedy selec tion. Homoeopathy is a holistic sci ence that takes into account even the smallest characteristics of the patient, unlike modern conventional medicine, where the doctor spends relatively little time with the patient. This article discusses the role of ho meopathic medicines for obsessive compulsive and related disorders.